2015
DOI: 10.1007/s11442-015-1241-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences of exergy use of cement manufacturing industry in China based on extended exergy accounting method

Abstract: Factory-level data from 23 provinces and some national statistical data in cement manufacturing industry and socio-economies in 2012 are used to analyze the spatial distribution of exergy use for China's cement manufacturing industry by the Extended Exergy Accounting method. This method takes full account of the inclusion of energy and raw material supply and other external factors (capital, labor and environment) into a comprehensive resource cost assessment. The extended exergy consumption and its intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Both factors impact coal consumption. Chen et al [11] analyzed the differences in coal consumption across various regions in the Chinese cement industry and found that the eastern region has the highest energy costs. Liu et al [12] analyzed the relationship between coal consumption and economic growth by constructing a panel data model of China's eastern, central, and western areas.…”
Section: Introductionmentioning
confidence: 99%
“…Both factors impact coal consumption. Chen et al [11] analyzed the differences in coal consumption across various regions in the Chinese cement industry and found that the eastern region has the highest energy costs. Liu et al [12] analyzed the relationship between coal consumption and economic growth by constructing a panel data model of China's eastern, central, and western areas.…”
Section: Introductionmentioning
confidence: 99%